OPTIMASI ALGORITMA SUPER ENKRIPSI UNTUK MENINGKATKAN PENGAMANAN DATA CITRA DIGITALDALAM PENGIRIMAN MMS PADA PIRANTI CERDAS - Setyaningsih, Emy; Iswahyudi, Catur; Widyastuti, Naniek (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2013)
Advances in technology have made communication and information technology functions into convergent and known as ICT (Information and Communication Technology). Internet and smart devices have an important role as a medium for multimedia convergence at this time. Mobile communications technology also developed rapidly, as well as the development of features that support services in the GSM system, among others, is MMS (Multimedia Messaging Service) that allows data transmission such as images, audio, and video.Computational complexity becomes an important concern in the development of cryptographic techniques on smart devices in the limited of bandwidth on wireless networks, also limited processing, memory, and time. This paper will discuss the security of image message using the concept of super encryption to optimize security of encryption key that adopts the concept of steganography method called End Of File (EOF). Applications built able to combine the speed, security, and flexibility so as to produce a good combination of speed, high security, complexity, reasonable computational overhead, and computational power.Image encryption algorithm is successfully implemented on a smart device with Android based operating system. Application also has the fastprocess and efficient computing resource. These are evidenced by the average time of encryption for image size of 256 x 256 pixels at 0.75 seconds and the image with a size of 480 x 640 pixels at 2.09 seconds. Average time decryption to image size of 256 x 256 pixels by 0.58 seconds and the image with a size of 480 x 640 pixels of 1.66 seconds.